Testes modais utilizando martelo instrumentado em estruturas de baixas freqüências naturais - Lima, Michelline Nery Azevedo (2006)
In this work it is discussed the improvement in the modal test for obtaining the Frequency Response Function (FRF) in low natural frequency structures by using as exciter an instrumented hammer. There are two conflicting needs in this kind of test: on the one hand, the low natural frequencies of the structure, which are usually associated with low damping, demand long acquisition time so that good resolution in the spectrum may exist. On the other hand, the sampling rate must be increased to correctly catch the short duration signal of the hammer. This leads to an elevated number of points in the signal to be acquired, and there may eventually be limitation on such number of points when using spectrum analyzers in the acquisition and obtaining of the FRFs. Thus, in this work, the selective decimation technique explored for the improvement of the test. The work includes the construction of a prototype with two degrees of freedom (S2GL) to serve as case study for the tests enabling the theoretical and experimental Frequency Response Functions (FRF) to be compared, as well as adjusting the parameters of the model. The MATLAB programming language was used for obtaining the FRFs. The efficiency of the improvement applied was verified through the frequency spectra, in which it was observed significant resemblance between the non-decimated FRF with the acquisition having a high number of points, and the decimated FRF with smaller number of points and selected so that it could preserve the correct detection of the hammer signal.